1996
DOI: 10.1136/jcp.49.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping position and upper airways bacterial flora: relevance to cot death.

Abstract: and storage iron concentrations in life and between blood ferritin and liver iron concentrations after death.'0 It is reasonable to suppose that if infants who die of SIDS are born with excess tissue iron stores then this would be reflected in the blood ferritin measured soon after birth.The availability of blood spots on stored Guthrie cards enabled us to compare blood ferritin concentrations in the first week of life from victims ofSIDS and controls. A significant difference might have formed the basis of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…In the second part of the study, in infants aged 12–18 months there were a number of observations which are pertinent to SIDS and the common bacterial toxin hypothesis. A prediction of the hypothesis is that when infants sleep prone secretions will pool in the upper airways leading to increased bacterial growth and toxin production [18]. If infants sleep supine, the secretions will drain under gravity into the oesophagus and bacterial growth will be less.…”
Section: Discussionmentioning
confidence: 99%
“…In the second part of the study, in infants aged 12–18 months there were a number of observations which are pertinent to SIDS and the common bacterial toxin hypothesis. A prediction of the hypothesis is that when infants sleep prone secretions will pool in the upper airways leading to increased bacterial growth and toxin production [18]. If infants sleep supine, the secretions will drain under gravity into the oesophagus and bacterial growth will be less.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study in adults with colds revealed increased bacterial growth in the upper respiratory tract (by nasal swabs) in individuals lying prone versus supine. 5 We believe the possible interrelationships between day care center-related SIDS, prone sleep position, and H pylori infection merit further investigation from multiple scientific disciplines.…”
Section: Sids Licensed Care Centers and Helicobacter Pylorimentioning
confidence: 99%
“…The above argument is theoretical but an investigation has been conducted in adult volunteers, aged 19–35 years, with colds [32]. They were asked to lie prone for 1 h and then supine for 1 h. At the end of each period, a nasal swab was obtained and bacterial counts were performed.…”
Section: Investigating the Hypothesismentioning
confidence: 99%